Korean Beauty Product Repurchase Intention Factors - Natalina Damayanthi; Albert Senoadji JR; Delivia Nurintan Tamara; Faranita Mustikasari (International Journal Labs, 2023)
In recent years, researchers have seen the increasing trends of people consuming Korean beauty products in Indonesia. The purpose of this research is to examine the determining factors of Indonesian consumer’s Korean beauty product repurchase intention. This research is based on quantitative research methods. Using a survey conducted with5-point Likert scale questionnaire. In total, 175 respondents filled the questionnaire from an undefined population through convenient sampling. The data is analysed with SEM-PLS Method using Smart PLS 4.0. The results of this study indicate the factors that influence Indonesian consumers to prefer buying Korean cosmetics over products from other countries. Based on the results, it can be concluded that Packaging Attractiveness, Attitude Towards The Product, Subjective Norms, Perceived Price, and Perceived Suitability are proven significant towards Repurchase Intention, while the most significant is Packaging Attractiveness. On the other hand, Product Variation is proven not significant. This paper is unique because it is the first to discuss the perceived suitability of Indonesian consumers towards Korean beauty products in the research model.